Propagação Vegetativa por Estacaria do Sobreiro (Quercus suber L.) - Cordeiro, Sonia; Moreira, Carmen; Ferreira, R. P.; Carvalho, J. P. F.; Pinto, T. M. S.; Pereira, J. M. G. Torres (Silva Lusitana, 2001)
The PAMAF-IED 8110 (1997-2000) project, was used to verify the rhizogenic capacity of Quercus suber, throughout the study of rhizogenic behaviour of different kinds of propagule considering several rooting factors. Due to the preliminary state of statistical data analysis, these conclusions are at an early stage, consisting only in first indications to a later definition of the best combination of "propagule x rooting factors"
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: propagule; Quercus Suber L; rooting factors

Propagação Vegetativa por Estacaria do Sobreiro (Quercus suber L.) (Silva Lusitana, 2001)
The PAMAF-IED 8110 (1997-2000) project, was used to verify the rhizogenic capacity of Quercus suber, throughout the study of rhizogenic behaviour of different kinds of propagule considering several rooting factors. Due to the preliminary state of statistical data analysis, these conclusions are at an early stage, consisting only in first indications to a later definition of the best combination of "propagule x rooting factors"